Design And Analysis Of Bearingless Permanent Magnet Synchronous Motor - N., Mamat; Kasrul, Abdul Karim; Zulkifilie, Ibrahim; Siti Azura, Ahmad Tarusan (UMPEDAC, University of Malaya, 2014)
Bearingless permanent magnet synchronous motor (BPMSM) has the characteristic of both conventional permanent magnet synchronous motor and traditional magnetic bearings. In this paper, the design and analysis of BPMSM by using Matlab/Simulink and ANSYS Maxwell are presented. The principle of electromagnetic force is utilized to ensure a stable levitation operation of BPMSM. The BPMSM mathematical model that has established to represent the dynamic of motoring force and radial suspension force is simulated in Matlab/Simulink environment. The ANSYS Maxwell, as an accurate finite element method (FEM) software in solving static, frequency-domain, and time-varying electromagnetic and electric fields is used to assist the development of BPMSM model before the integration with the control system is performed. The excitation of motoring winding and suspension winding are independently controlled through separate PI controller. The applications of BPMSM are suitable for high speed electrical machines such as compressors, turbines, pumps, and mixers.